123k views
4 votes
What is the product?

(negative 3 s + 2 t)(4 s minus t)

negative 12 s squared minus 2 t squared
negative 12 s squared + 2 t squared
negative 12 s squared + 8 s t minus 2 t squared
negative 12 s squared + 11 s t minus 2 t squared

User Gulz
by
4.7k points

2 Answers

7 votes

Answer:

option 4 is the answer

Explanation:

User MendyK
by
5.1k points
1 vote

Answer:

(d) negative 12 s squared + 11 s t minus 2 t squared is the PRODUCT.

Explanation:

Here, the given expression is:

(negative 3 s + 2 t)(4 s minus t) = (- 3s + 2t) (4s - t)

Now, by DISTRIBUTIVE PROPERTY:

A(B-C) = AB - AC

Simplifying the given expression ,we get:


(- 3s + 2t) (4s - t)  = -3s(4s-t) + 2t(4s -t)\\= -3s(4s) -3s(-t) + 2t(4s) + 2t(-t)  = -12s^2 + 3st + 8 st - 2t^2\\= -12s^2 + 11st - 2t^2\\\implies (- 3s + 2t) (4s - t)  =   -12s^2 + 11st - 2t^2

Now, the resultant expression can also be written as


-12s^2 + 11st - 2t^2 = negative 12 s squared + 11 s t minus 2 t squared.

Hence, the option (4) is the correct option.

User Kevinw
by
5.3k points